Modern Introduction to Surface Plasmons : Theory, Mathematica Modeling, and Applications / [electronic resource] - Sarid, Dror; Challener, William (Cambridge : Cambridge University Press, 2010)
Introducing graduate students in physics, optics, materials science and electrical engineering to surface plasmons, this book also covers guided modes at planar interfaces of metamaterials with negative refractive index. The physics of localized and propagating surface plasmons, on planar films, gratings, nanowires and nanoparticles, is developed using both analytical and numerical techniques. Guided modes at the interfaces between materials with any combination of positive or negative permittivity and permeability are analyzed in a systematic manner. Applications of surface plasmon physics are described, including near-field transducers in heat-assisted magnetic recording and biosensors. Resources at www.cambridge.org/9780521767170 include Mathematica code to generate figures from the book, color versions of many figures, and extended discussion of topics such as vector diffraction theory.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Plasmons (Physics); Plasma oscillations; Surfaces (Physics)